Panomics: New Databases for Advancing Cardiology - Vakili, Dara; Radenkovic, Dina; Chawla, Shreya; Bhatt, Deepak L. (Frontiers in Cardiovascular Medicine, 2021)
The multifactorial nature of cardiology makes it challenging to separate between noisy signals from confounders and real markers or drivers of disease. Panomics, the combination of various omic methods, provides the deepest insights into the underlying biological mechanisms to develop tools for personalised medicine under a systems-biology approach. Questions remain about current findings and anticipated developments of omics. Here we search for omic databases, investigate, the types of data they provide, and give some examples of panomic applications in healthcare. We identified 104 omic databases, of which 72 met inclusion criteria: genomic and clinical measurements on a subset of the database population plus one or more omic datasets. Of those, 65 were methylomic, 59 transcriptomic, 41 proteomic, 42 metabolomic, and 22 microbiomic databases. Larger database sample sizes and longer follow-up are often better suited for panomic analyses due to statistical power calculations. They are often more complete, which is important when dealing with large biological variability. Thus, the UK BioBank rises as the most comprehensive panomic resource, at present, but certain study designs may benefit from other databases.